2017
DOI: 10.1093/ijnp/pyx064
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Brief Mindfulness Training Reduces Alcohol Consumption in At-Risk Drinkers: A Randomized Double-Blind Active-Controlled Experiment

Abstract: BackgroundLike other complex psychosocial interventions, mindfulness-based treatments comprise various modality-specific components as well as nonspecific therapeutic ingredients that collectively contribute to efficacy. Consequently, the isolated effects of mindfulness strategies per se remain unclear.MethodsUsing a randomized double-blind design, we compared the isolated effects of 11-minutes of “supervised” mindfulness instruction against a closely matched active control (relaxation) on subjective, physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 80 publications
0
31
0
7
Order By: Relevance
“…It is possible that more pronounced effects on binge eating might have emerged with out-of-session practice of the allocated strategy. For example, we have recently shown that pronounced behavioural effects of a related strategy (mindfulness) only emerged after a one week period, when participants (heavy drinkers) had been given the opportunity to further develop their self-regulation skills (Kamboj et al, 2017). Future studies should also consider the additional control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that more pronounced effects on binge eating might have emerged with out-of-session practice of the allocated strategy. For example, we have recently shown that pronounced behavioural effects of a related strategy (mindfulness) only emerged after a one week period, when participants (heavy drinkers) had been given the opportunity to further develop their self-regulation skills (Kamboj et al, 2017). Future studies should also consider the additional control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were then fitted with the Firstbeat device and their HRV was measured during an initial 5-minute baseline period and throughout the rest of the experiment (Kamboj, Irez et al 2017). After the baseline measure of HRV, participants completed the negative mood induction task (the 'failure version' of the Remote Associates Test), followed by the compassion or self-critical ruminative strategy.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Similarly, mindfulness training was shown to reduce stress (Brewer et al, 2009;Garland et al, 2010), craving and risk of relapse (Bowen et al, 2014;Zgierska et al, 2009) in recovering substance dependent individuals. However, it is important to note, that mindfulness as a treatment approach to reduce alcohol craving might not be observed following a single intervention (Caselli et al, 2016;Kamboj et al, 2017;Murphy and MacKillop, 2014;Vinci et al, 2014), but instead could arise from repeated practices. Decreased craving and prolonged alcohol abstinence as a result of longterm practices, further supports the notion that mindfulness benefits occur as a result of plastic brain changes within prefrontal-amygdala circuitry (Doll et al, 2016;Gotink et al, 2016).…”
Section: Interoceptive Training In Alcohol Misusementioning
confidence: 99%
“…General trauma symptoms (previous 7 days) were assessed using the 22-item Impact of Events Scale (IES; (Weiss, 2007) adapted for the trauma-film (Holmes et al, 2009). Heart rate (HR) was recorded using a BodyGuard-2 ECG device (FirstBeat Technologies, Finland), and episodic blood pressure with a BM40 XL device (Beurer UK) as outlined elsewhere (Kamboj et al, 2017). Event markers corresponding to the start of the film and end of the 1 hr filler period were recorded to identify the 5-min pre-film and post-drug periods (T1 and T3 as described in the main paper and Figure 1).…”
Section: Questionnaire and Physiological Assessmentsmentioning
confidence: 99%